Patterns of type 2 diabetes risk factors using latent class analysis (LCA) model: a population-based study in the South of Iran, Kharameh cohort population - Ariamanesh, Yasaman; Vali, Mohebat; Rezaianzadeh, Abbas; Ghaem, Haleh (BMC public health, 2025)
Background Type 2 Diabetes (T2D) is a prevalent chronic disorder that decreases life expectancy and increases mortality. This study sought to identify the latent class (LC) patterns of risk factors for T2D in the Kharameh cohort population. Methods This population-based study used baseline data from the Kharamah cohort, which included 9,022 participants after excluding those with pre-existing or baseline-diagnosed T2D. Latent Class Analysis (LCA) was applied to categorize subgroups of T2D risk factors within the population. Results This study analyzed 9,022 participants (47.0% male, 53.0% female) after excluding pre-existing diabetes and those with Fasting Blood Sugar (FBS) ≥ 125 mg/dL at baseline (diagnosed as diabetic at study entry). The largest age group was 40–49 years (47.0%). Among all participants, 23.0% had hypertension, 6.8% exhibited high total cholesterol, 19.5% had high FBS, and 69.6% had abdominal obesity. Additionally, 25.4% were smoking status, 4.0% reported alcohol consumption, and 52.0% engaged in high or severe levels of physical activity. LCA identified three distinct classes: 1. Low-Risk (about 33.0%): Individuals engaging in high/severe physical activity, 2. Clinical-Risk (about 6.0%): Those with abnormal lipid profiles and elevated FBS, 3. Lifestyle-Risk (about 61.0%): Individuals exhibiting an unhealthy lifestyle. Conclusions This study’s central finding highlights the pivotal role of physical activity in preventing or delaying the onset of T2D. Therefore, promoting physical activity, in collaboration with managing clinical and lifestyle risk factors, is essential for preventing and effectively managing T2D.